Bestseller and Blockbuster Culture. Introduction - Agger, Gunhild; Grøn, Rasmus; Nielsen, Hans Jørn; Wade, Anne Marit (Academic Quarter | Akademisk kvarter, 2013)
Bestseller and blockbuster culture includes new ways of producing, distributing and experiencing media. Bestseller and blockbuster productions encompass production values in which a new type of pragmatic cooperation with external partners takes place. Films and television series are produced as platform productions for different media (cinema, television, mobile media) in combination with merchandise, franchising and destination tourism. To an increasing degree, books are published as e-books, thus contributing to changes in the culture of reading. Various agents and platforms contribute to new distributive modes of bestseller and blockbuster productions: publishers, bookshops, libraries, the DVD-market, online television channels and international cooperation agents. The phenomenon of bestseller and blockbuster culture is the subject of investigation in this volume of Academic Quarter.